Auditory perception in individuals with Friedreich’s Ataxia - G, Rance; L., Corben; E., Barker; P., Carew; D., Chisari; M., Rogers; R., Dowell; Jamaluddin, Saiful Adli; R., Bryson; M.B., Delatycki; ,; , (Karger, 2010)
INTRODUCTION: Friedreich's ataxia (FRDA) is an inherited ataxia with a range of progressive features including axonal degeneration of sensory nerves. The aim of this study was to investigate auditory perception in affected individuals.